2014
DOI: 10.1016/j.febslet.2014.04.026
|View full text |Cite
|
Sign up to set email alerts
|

The role of commensal bacteria in the regulation of sensitization to food allergens

Abstract: The prevalence of life-threatening anaphylactic responses to food is rising at an alarming rate. The emerging role of the gut microbiota in regulating food allergen sensitization may help explain this trend. The mechanisms by which commensal bacteria influence sensitization to dietary antigens are only beginning to be explored. We have found that a population of mucosa-associated commensal anaerobes prevents food allergen sensitization by promoting an IL-22-dependent barrier protective immune response that lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 105 publications
4
43
0
3
Order By: Relevance
“…2b, 4), in agreement with both human and animal studies, supporting an important role of this bacteria class in relation to allergy [15, 21, 22]. Clostridia bacteria are anaerobic spore-forming Firmicutes bacteria, which is a dominant class of commensal bacteria, residing in close proximity to the colonic epithelium [18]. This may explain why the colon was the most sensitive segment in which to detect changes for the Clostridia OTUs (see below).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…2b, 4), in agreement with both human and animal studies, supporting an important role of this bacteria class in relation to allergy [15, 21, 22]. Clostridia bacteria are anaerobic spore-forming Firmicutes bacteria, which is a dominant class of commensal bacteria, residing in close proximity to the colonic epithelium [18]. This may explain why the colon was the most sensitive segment in which to detect changes for the Clostridia OTUs (see below).…”
Section: Discussionsupporting
confidence: 54%
“…Food allergy develops following loss of oral tolerance, which allows allergic sensitization [17]. Since barrier integrity and function is important to maintain oral tolerance to proteins, the known role of the microbiome in maintaining the barrier homeostasis is probably important to reduce allergen uptake and/or allergen interaction with the epithelial and immune cells [6, 18]. Further, metabolites produced by the microbiota can affect immune cell function directly, like for instance the reported effects of short-chain fatty acids (SCFAs) protecting against oral sensitization in mice by numerous pathways in the gastrointestinal tract, including IgA production, CD103+ dendritic cells [19], and regulatory T cell function [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rising disease prevalence over a short period cannot be explained by genetic variation alone, renewing interest in the role of the environment in shaping allergic sensitization to food (2,3). First proposed more than 20 years ago, the hygiene hypothesis suggested that societal efforts to reduce exposure to infectious microbes early in life have deprived the immune system of immunoregulatory stimulation necessary for protection against allergic disease (4).…”
mentioning
confidence: 99%
“…In the USA, in 2009-2010, 8% of children were estimated to have food allergy, and 39% of these children experienced severe reactions [2]. Moreover, the prevalence of food allergy in the USA, UK and China appears to have doubled or tripled over the past 12 years, likely related to environmental changes, for example, decreased prevalence of certain infections or alterations in the intestinal microbiome [3][4][5]. Furthermore, the increasing prevalence coupled with the absence of effective therapies, other than avoidance of the offending food and prompt treatment of allergic reactions that develop after accidental ingestion, renders food allergy as an urgent clinical problem.…”
mentioning
confidence: 99%